GAMBARAN MANAJEMEN PENGELOLAAN LINEN PASIEN DENGAN KESESUAIAN STANDAR PELAYANAN MINIMAL DI RUMAH SAKIT JIWA MUTIARA SUKMA PROVINSI NTB TAHUN 2024 - Widya Puspita Dewi; Abdul Aziz Fatryawan (Nusadaya Journal of Multidiciplinary Studies, 2024)
Linen is an indicator of minimum hospital service standards in laundry installations. Standards for linen services are regulated in the Decree of the Minister of Health of the Republic of Indonesia No.129 of 2008 concerning Minimum Service Standards for Hospitals in accordance with the mandate of Law No.44 of 2009 concerning hospitals which states that hospitals must have service standards as a reference that must be achieved in implementing every aspect of implementation activities. The stages of hospital linen management consist of the stages of collecting linen, receiving linen, washing linen, storing linen, distributing linen, and transporting linen. Laundry services in hospitals have two indicators in the Minimum Service Standards, namely the absence of lost linen and the timely provision of linen for inpatient care, each of which is 100%. This research aims to determine the management description of patient linen management in accordance with minimum service standards at Mutiara Sukma Mental Hospital, NTB Province in 2024. This research is descriptive research using a quantitative approach, in the form of observation, documentation and questionnaires. Linen management in accordance with minimum service standards at the Mutiara Sukma Mental Hospital, NTB Province, has met the standards according to Ministerial Decree No. 17 concerning Hospital Environmental Health regarding the management of linen in hospitals starting from the process of collecting, receiving, washing, distributing and transporting. And based on Minister of Health Decree No.129/Menkes/SK/II/2008 concerning Minimum Service Standards where the indicators guarantee that there is no lost linen that has reached standards seen from several factors, namely human resources, facilities and infrastructure, policies (SOP), and minimum service standards (SPM) for linen.